Prevalence of cumulative trauma disorders among office workers in a semiconductor industry - Mohd Yusuff, Rosnah; Abdullah, Airing Zairose (2010)
The health records of the employees in a semiconductor industry showed a drastic increase of musculoskeletal disorders for 2007 compared to 2005 and 2006. This may have a significant effect not only to the employees but also to the organization. If these problems remain unsolved, this may lead to poor work performance, increase medical leave, lower productivity and increase of health compensation claims. A study was conducted to determine the existence of cumulative trauma disorders among the office employees, identi-fy level of severity and what are the probable factors that contribute to cumulative trauma disorders. A survey questionnaire, interviews and observation methods were used to identify the problems and to provide recom-mendations to prevent or rapidly response to work related upper limb disorders. Based on these probable fac-tors, some suggestions and recommendations were proposed to reduce cumulative trauma disorders risks.